Learning the Culture of Chinese Indonesian Community through the Documentary Film “Once Upon a Time in Chinatown” - Septerianie Sutandi; Selvia (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Chinese Indonesian has a very diverse culture. On the other hand, people who are interested in Mandarin and Chinese culture in Indonesia are also increasing. Chinese Indonesian community contributes and has a big role in Indonesian history. The learning media used to study Chinese culture are very diverse, one of which is using documentary films. The purpose of this research is to find out the Chinese Indonesian community values that can be learned by the general public from the film "Once Upon a Time in Chinatown", as well as to identify how the film can be used as a medium for learning the culture of the Indonesian Chinese community. Researchers uses a qualitative descriptive method to analyze the cultural data of the Chinese Indonesian in each episode of the documentary film. The result of this research show that a lot of Chinese culture, especially in the culinary field, has been acculturated with Indonesian culture, has given a new color to Indonesian culture and other aspects of life. This documentary film fulfills the characteristics of documentary films as a Chinese Indonesian culture learning media because it prioritizes conveying the reality and processes of past events as scientific information, conveying messages, positive mental attitudes, and norms that should be imitated.